Synergism Between Interleukin (IL)-17 and Toll-like Receptor 2 and 4 Signals to Induce IL-8 Expression in Cystic Fibrosis Airway Epithelial Cells - Shota Mizunoe; Tsuyoshi Shuto; Shingo Suzuki; Chizuru Matsumoto; Kenji Watanabe; Keiko Ueno-Shuto; Mary Ann Suico; Kouhei Onuki; Dieter C. Gruenert; Hirofumi Kai (Elsevier, 2012)
Cystic fibrosis (CF) is the most common lethal inherited disorder and is caused by mutations in the gene encoding the CF transmembrane regulator (CFTR). The CF lung expresses a profound proinflammatory phenotype that appears to be related to a constitutive hypersecretion of interleukin (IL)-8 from airway epithelial cells in response to microbial infection. Since overproduction of IL-8 in CF contributes to massive bronchial infiltrates of neutrophils, identification of the pathways underlying IL-8 induction could provide novel drug targets for treatment of neutrophil-dominated inflammatory diseases such as CF. Here, we show that IL-17A synergistically increases IL-8 production induced by a toll-like receptor (TLR) 2 agonist, peptidoglycan (PGN), or TLR4 agonist, lipopolysaccharide (LPS), in a human CF bronchial epithelial cell line (CFBE41o-). A strong synergism was also observed in primary human CF bronchial epithelial cells, but not in human non-CF cell lines and primary cells. Notably, despite the induction of nuclear factor-κB and MAP kinases during TLR2 or TLR4 activation in CFBE41o-, IL-17A-dependent synergism appears to be the result of enhanced PGN- or LPS-induced phosphorylation of p38. Taken together, these studies provide evidence that IL-17A is a critical factor in increasing IL-8 expression in bacteria-infected CF airways via a pathway that regulates p38 phosphorylation. Keywords:: interleukin (IL)-17, toll-like receptor 2 and 4 (TLR2/TLR4), IL-8, cystic fibrosis (CF), p38